2014
DOI: 10.1089/ars.2013.5358
|View full text |Cite
|
Sign up to set email alerts
|

Secisbp2 Is Essential for Embryonic Development and Enhances Selenoprotein Expression

Abstract: In hepatocyte-specific conditional mouse models, Secisbp2 gene inactivation is less detrimental than tRNA[Ser]Sec inactivation. A role of Secisbp2 in stabilizing selenoprotein mRNAs in vivo was uncovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 63 publications
2
62
1
Order By: Relevance
“…Secisbp2 is essential for embryonic development [24]. In order to investigate its function in neurons, we specifically inactivated the Secisbp2 gene by an out-of-frame deletion of exon 5 using a CamK-Cre transgene (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Secisbp2 is essential for embryonic development [24]. In order to investigate its function in neurons, we specifically inactivated the Secisbp2 gene by an out-of-frame deletion of exon 5 using a CamK-Cre transgene (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Transgenic Secisbp2 tm1a(EUCOMM)Wtsi mice were described recently [24]. The breeding colony was maintained on breeding diets (Ssniff, Soest, Germany) containing on average 0.2-0.3 ppm Se.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further analyze SBP2 function in organs not accessible in patients, mice models have been developed. While gene inactivation leads to embryonic lethality (123), the conditional deletion of SBP2 is less detrimental than Sec-tRNA [Ser]Sec inactivation and provides a tool for further in vivo functional analysis (124).…”
Section: The Secis Binding Protein 2 (Sbp2)mentioning
confidence: 99%
“…We have previously reported that hepatocyte-specific inactivation of selenoprotein translation abrogated hepatic deiodinase activity in Alb-Cre ; Trsp fl/fl mice [13]. Expression of all selenoproteins is quantitatively abolished in livers of Alb-Cre ; Trsp fl/fl mice [15]. Ablation of selenoprotein biosynthesis in hepatocytes does not lead to liver failure or other diseases [16,17].…”
Section: Resultsmentioning
confidence: 99%